Synthesis of problematization in learning electricity and electrical circuits in university contexts - Ángel Hernando Palacios (Corporación Universitaria Minuto de Dios, 2014)
Learning about electricity and electrical circuits, has been a subject of interest in different research areas in education and engineering. Consequently, the problems that arise are usually regarded as common in accordance to the research background on this issue. Accordingly, trends, jobs and development are found that are subject to be collected and synthesized in order to make contributions and enriching to do are teaching and learning strategies.